Pre-Mashtotsian Script Deciphered: Insights from an Ancient Colony - Beckham, Shayne (Bulletin of Yerevan University B: Philology, 2024)
Mashtots’ invention of the modern Armenian alphabet in the fourth century CE is the earliest currently recognized form of Armenian alphabet. This study looked at the research question: Is it possible to reconstruct the alphabet that laid the foundation for the Mashtotsian script? Candidate rock engravings and pictograms of Greater Armenia from the fifth to the second millennia BCE cover various communication eras and scripts, and a lack of multilingual inscriptions makes the task difficult, but not impossible. Verbal desinential evidence connects mid-Holocene Greater Armenia and Southeast Asia including Australia via a linguistic substratum. Using this knowledge, an ocher painting on a cave wall in Australia became the focus, with what appears to be a form of Armenian script. Furthermore, the dot number system used in the painting corresponds to the deeply rooted and unique Biainian number system employed in Greater Armenia. Hypothesizing from the Armenian religious artistic style that a script above the pictographic subject’s head is his name, the letters could be reconstructed. From those letters, it was hypothesized there was late vocalic development, and the original consonants were 90° right rotated compared to the modern forms. On this basis, it was possible to decipher the ancient script on a one of a kind menhir found in Shamiram. In total, eight of the original 22 letters were reconstructed, enough to give a feel for pre-Mashtotsian historical phonology, which caused the original alphabet to fall into disuse.